FGF23 expression in rodents is directly induced via erythropoietin after inhibition of hypoxia inducible factor proline hydroxylase - Flamme, Ingo (PLoS One, 2017)
Plasma levels of FGF23 are increased in patients with chronic kidney disease. Beside its role in phosphate homeostasis, iron deficiency and anemia are associated with increased FGF23 plasma levels. Recently, FGF23 plasma levels were shown to be increased in mice after treatment with hypoxia inducible factor-proline hydroxylase (HIF-PH) inhibitors which are strong inducers of erythropoietin and erythropoiesis and are known to modulate iron uptake and availability. Therefore we investigated a potential context between expression of FGF23 and stimulation of erythropoiesis using a HIF-PH inhibitor and erythropoietin in rats. FGF23 plasma levels are induced at peak levels 2 h after intravenous injection of recombinant human Erythropoietin (rhEPO). Likewise induction of endogenous EPO using a HIF-PH inhibitor (BAY 85–3934) is followed by an increase of FGF23 plasma levels. In contrast to rhEPO the HIF-PH inhibitor induces lower peak levels of FGF23 applying equivalent hematopoietic doses. Bone and bone marrow were identified as sources of EPO-induced FGF23. Immediate induction of FGF23 mRNA was also detected in EPO receptor positive murine hematopoietic BAF3 cells after treatment with rhEPO but not after treatment with the HIF-PH inhibitor. Pretreatment of mice with a neutralizing anti-EPO antibody abrogated FGF23 induction by the HIF-PH inhibitor. Thus, direct impact on FGF23 expression by HIF-PH inhibition in vivo via hypoxia mimicking and modulation of iron metabolism appears unlikely. Collectively, the findings point to an EPO dependent regulation pathway of FGF23 gene expression which might be important in the context of erythropoiesis stimulating therapies in patients with renal anemia.